Illuminating oncology research by bioluminescent imaging - Tryambak Pratap Srivastava; Ruby Dhar; Om Saswat Sahoo; Hiya Aidasani; Avdesh Rai; Kumar, Arun; Subhradip Karmakar (Asian Journal of Medical Sciences, 2023)
Bioluminescent imaging (BLI) has emerged as a powerful tool in cancer research, allowing for non-invasive, real-time monitoring of various aspects of cancer biology in vivo. This technique relies on the expression of bioluminescent reporter genes in cancer cells, enabling the visualization of tumor growth, metastasis, and response to treatment. In this review, we provide an overview of the principles underlying BLI, its applications in cancer research, and the potential advantages and limitations of this technology.